Rhetorical Persuasion in Sara Duterte’s Basic Education Curriculum Advocacy: A Sociopragmatic Analysis - Abregana, Geterel John; Mabale, Almira Luz; Mendiola, Laica; Syting, Christian Jay (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aimed to describe the pragmatic features of Sara Duterte's advocacies regarding the Basic Education Curriculum in the Philippines. The research data, gathered from 2022 to 2023 during Duterte's tenure as Secretary of the Department of Education, included an interview and speeches totaling 5 hours and 16 minutes. Using dimensions of pragmatics, including presupposition (Stalnaker, 1973), implicature (Grice, 1975), felicity conditions (Searle, 1969), and politeness strategies (Brown & Levinson, 1987), the analysis revealed several key findings. The presuppositions identified included learner success and employability, inclusive education, a supportive learning environment, teacher support and development, education system improvement, and learner values and development. Implicatures conveyed messages of resiliency, heroic qualities, perseverance, and involvement beyond education. The illocutionary forces identified were assertives, directives, and commissives, each examined for adherence to the conditions necessary for their validity. Additionally, Duterte strategically employed politeness strategies such as positive politeness, negative politeness, bald-on-record, and off-record strategies. These findings offer a deeper understanding of how political figures strategically use language to shape public opinion and policy agendas, particularly in critical areas such as education. By comprehending the pragmatic underpinnings of political discourse, stakeholders can better discern the intentions and potential impacts of such advocacies, facilitating informed decision-making and societal progress.